Relationship between Human Resource Development, Work Discipline on Nurse Performance at Hermina Jatinegara Hospital - Nainggolan, Dedy Santoso; Sihombing , Christina N.; Siagian , Jonny (Fundamental Management Journal, 2024)
HR developments is a manifestation of efforts to developed the qualities of human resources capabilities through various processes of educational planning methods, training, and managements of personel or employee to achieving a satisfactory result. The quality of health services provided by nurses is determined by their performance, so in order to maintain a better quality of service, one of benchmark in assessing qualities of nursing service in hospital is to assess performance of nursing service in hospital rooms. These studies aim to determining partial and simultaneous relationships between development of human resources and work discipline on the performance of nurses at Hermina Jatinegara Hospital. Data collections technique in these studies was a questionnaire. Population of these studies were all nurses at Hermina Jatinegara Hospital inpatient work units, totaling 30 peoples with the overall sampling or saturate sample. The type of research use in these studies is a quantitative approach, by tested probability value of Spearman rank correlation significance, by tested validity and reliability of statements item for each variable and t test and f test which are process use SPSS version 27 programs. The result of these studies indicating that partially developments of human resource is significant relate to performances of nurse indicate by a significances value of 0.000 ≤ 0.05, then partially work discipline is significant relate to performances of nurse indicate by a significances value of 0.000 ≤ 0.05, then simultaneously the development of human resources and work discipline has a significant relationship with nurse performance shown with a significances value of 0.000 ≤ 0.05. The author's suggestion in these studies is that Hermina Jatinegara Hospital can provide development training to support nurse skills, evaluate nurse work time and provide assistance by supervisors to support nurse performance. Keywords: Human Resource Development, Work Discipline, and Performance